2011
DOI: 10.1149/2.019201jes
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Cu Substrates with W Addition for Vertical Structure Light Emitting Diodes using Electroplating Method

Abstract: Pure Cu substrate has been previously electroplated on p-GaN side of vertical structure GaN-based light emitting diode (LED) to mechanically hold thin GaN-based multilayer after removal of a sapphire substrate by laser lift-off process. The ductile Cu substrate needs to be mechanically strengthened to prevent the GaN-based multilayer from being damaged during vertical LED chip fabrication. In this study, the formation of Cu substrate with W addition on Au-seeded LED wafer by electroplating is introduced. W pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Our recent work showed that Cu substrate with a uniform distribution of WO 3 particles can be formed by electrodeposition method. 12 The residual stress of the WO 3 -added Cu substrate was managed to be almost zero, and moreover its electrical resistivity was not increased much from that of pure Cu substrate, in spite of adding WO 3 particles. The main benefit of using the WO 3 -added Cu substrate is to enhance the mechanical strength of Cu substrate by at least 1.5 times by adding less than 2.0 at% W as WO 3 .…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Our recent work showed that Cu substrate with a uniform distribution of WO 3 particles can be formed by electrodeposition method. 12 The residual stress of the WO 3 -added Cu substrate was managed to be almost zero, and moreover its electrical resistivity was not increased much from that of pure Cu substrate, in spite of adding WO 3 particles. The main benefit of using the WO 3 -added Cu substrate is to enhance the mechanical strength of Cu substrate by at least 1.5 times by adding less than 2.0 at% W as WO 3 .…”
Section: Resultsmentioning
confidence: 91%
“…Conditions for electrodepositing stress-free Cu and WO 3 -added Cu substrates can be found in our previous works. 7,12 A 248-nm KrF excimer laser was irradiated through the transparent sapphire substrate at an energy density of 0.3 J cm −2 to remove the sapphire substrate. An n-electrode of Ti (20 nm)/Al (20 nm)/Au (300 nm) was deposited on n-GaN surface exposed after etching the buffer GaN layer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 We also found that adding less than 2 at% W as WO 3 in pure Cu substrate by electrodeposition method could improve its hardness considerably. 7 It was also previously reported that the electrodeposition of pure Cu with higher mechanical strength and lower electrical resistivity can be achieved with high density of nanotwins. 8,9 In this study, we propose the electrodeposition of Cu-Co alloy substrate for vertical structure GaN-based LEDs.…”
mentioning
confidence: 85%
“…The use of electroplating technology has improved the performance of GaN-based LEDs in solid-state lighting applications [1][2][3][4]. However, using electroplating technology adds an extra process to LED manufacturing because laser lift-off (LLO) technology must be used, causing LED manufacturers have low throughput, low yield, and high cost.…”
Section: Introductionmentioning
confidence: 99%